Effects of climate conditions in formation and development of Zonuz's historical garden city architecture - Zonouz, Hassan Khalili (Journal of Architecture and Urbanism, 2015)
Zonuz architecture has originated from prehistoric era by having worthwhile architectural signs of the Kura – Aras culture related to Bronze Age (3800 BC), as seen in Qiz Qala and Oğlan Qalasi, located about 5 km from the city. This architecture by the dry stone method is standing at the top of the mountain and has been made of field stone which was undoubtedly outstanding in its period. This technique has reached its style as back to back diagonal stones placed within 30–45 different degrees among them with respect to the wall making evolution during the period of 6000 years. This method has been used in all buildings and walls of house-gardens of the city for millenniums appropriately. The technique reveals that instead of brick, natural elements with more resistance have been applied. Availability of travertine is the reason of using it along with mortar in order to constructing the entire city and many other buildings. However, in some cases like Qizil-Korpi bridge plaster has been used and in some others – that needed more strength – a composition of lime and clay is applied. But it can be acknowledged that the structure of the building and foundations is part of the natural environment. Urban areas in this location have developed condition of constructing new architecture and house-garden urban engineering in terms of more convenient natural situation including better utilizing sun light, more appropriate slope as well as plenty of springs – about 360. This is a city with spatial shape which is integrated with natural beauty of Azerbaijan and has created a rare house-garden quality. Although urban engineering and architecture of this city have got an outstanding index and many articles have been published in the field of Geology, Geography, Philosophy and so on, but nothing can be found about its architectural report, techniques and thoughts throughout the resources. The aim of present research is based on finding out topography and climate conditions effecting the architecture and city planning; in this article the author also tries to mention Zonuz architecture and type of architectural spaces and its structures in order to make a better understanding and increasing sensitivity about the building and urban setting, conservation and restoration. In order to come to a conclusion we had to choose a method for this subject and going through library shelves seemed to be real poor; hence we had to do site study and consider actual cultural, technical and historical cases and their relation with topography and city planning.